2009
DOI: 10.1016/j.ecolecon.2009.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Long-run determinants of pollution: A robustness analysis

Abstract: This paper examines how robust economic, political, and demographic variables are related to water and air pollution. Employing Bayesian Averaging of Classical Estimates (BACE) for a cross section of up to 74 countries, 33 variables and 3 proxies for air and water pollution over a period from 1980 to 1995 we confirm the Environmental Kuznets Curve hypothesis, highlight the relevance of efficient production technologies and underline the role of political and demographic variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(18 citation statements)
references
References 48 publications
2
14
0
Order By: Relevance
“…They used a sample of 42 developing economies for the period 1971-9991 and showed that per capita emissions of carbon monoxide, sulphur dioxide, nitrous oxide and particulate matter exhibit negative relationships with per capita GDP. In recent years, the existence of the EKC was also confirmed by other studies such as Lamla [28], Apergis and Ozturk [29] and Jebli et al [30]. However, the evidence remains mixed.…”
Section: Literature Review: Renewable Energy Development and Economicsupporting
confidence: 52%
“…They used a sample of 42 developing economies for the period 1971-9991 and showed that per capita emissions of carbon monoxide, sulphur dioxide, nitrous oxide and particulate matter exhibit negative relationships with per capita GDP. In recent years, the existence of the EKC was also confirmed by other studies such as Lamla [28], Apergis and Ozturk [29] and Jebli et al [30]. However, the evidence remains mixed.…”
Section: Literature Review: Renewable Energy Development and Economicsupporting
confidence: 52%
“…This method was suggested by (Sala-i-Martin et al, 2004) and is an approximation of the earlier Bayesian model averaging (BMA) technique presented by (Fernández, Ley and Steel, 2001). In BACE, we use Schwarz approximation to compute the probability of competing models and determinants (see: Lamla, 2009;Simo-Kengne, 2016).…”
Section: Methodological Backgroundsmentioning
confidence: 99%
“…Under environmental degradation, the working class is more vulnerable and subject to higher costs than the wealthy (Benton, 1997). Therefore, a left‐wing government is more prone to putting forward strict environmental protection policies to shield the interests of their supporters (Lamla, 2009). In contrast, as environmental regulation costs are often born by entrepreneurs and capitalists, right‐wing parties are less willing to implement stringent environmental protection policies (Potrafke, 2010; Chang and Berdiev, 2011).…”
Section: Democracymentioning
confidence: 99%